Cost-effectiveness analysis of cetuximab combined with chemotherapy as a first-line treatment for patients with RAS wild-type metastatic colorectal cancer based on the TAILOR trial. Issue 2 (12th February 2020) - Wang, Huijuan; Huang, Lingfei; Gao, Peng; Zhu, Zhengyi; Ye, Weifeng; Ding, Haiying; Fang, Luo
Abstract : Objectives: Cetuximab plus leucovorin, fluorouracil and oxaliplatin (FOLFOX-4) is superior to FOLFOX-4 alone as a first-line treatment for patients with metastatic colorectal cancer with RAS wild-type (RAS wt mCRC), with significantly improved survival benefit by TAILOR, an open-label, randomised, multicentre, phase III trial. Nevertheless, the cost-effectiveness of these two regimens remains uncertain. The following study aims to determine whether cetuximab combined with FOLFOX-4 is a cost-effective regimen for patients with specific RAS wt mCRC in China. Design: A cost-effectiveness model combined decision tree and Markov model was built to simulate pateints with RAS wt mCRC based on health states of dead, progressive and stable. The health outcomes from the TAILOR trial and utilities from published data were used respectively. Costs were calculated with reference to the Chinese societal perspective. The robustness of the results was evaluated by univariate and probabilistic sensitivity analyses. Participants: The included patients were newly diagnosed Chinese patients with fully RAS wt mCRC. Interventions: First-line treatment with either cetuximab plus FOLFOX-4 or FOLFOX-4. Main outcome measures: The primary outcomes are costs, quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratios (ICERs). Results: Baseline analysis disclosed that the QALYs was increased by 0.383 caused by additional cetuximab, while an increase of US62 947 was observed in relation to FOLFOX-4 chemotherapy. The ICER was US164 044 per QALY, which exceeded the willingness-to-pay threshold of US28 106 per QALY. Conclusions: Despite the survival benefit, cetuximab combined with FOLFOX-4 is not a cost-effective treatment for the first-line regime of patients with RAS wt mCRC in China. Trial registration number: TAILOR trial (NCT01228734 ); Post-results.